2017
DOI: 10.5430/ijhe.v6n5p14
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Practices of University Students Living in Residence

Abstract: Sleep plays an important role in both students' academic and personal life. Despite widespread sleep problems among young adults, few studies focus on higher education students living in campus residence. This study investigated residence-living students' sleep patterns, sleep promoting practices, sources of help seeking, and preferred ways to receive information. Results highlighted that 66.8% of the participants did not think they had enough sleep. However, only 18.9% of the students sought help. The campus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…These sessions improved nursing students' knowledge on the importance of adopting healthy sleep hygiene practices for better sleep quality and enhanced academic performance. This finding is relatively in harmony with a study accomplished in Canada, where it was promising to find that most students reported meeting the basic needs of sleep hours and used some strategies to help their sleep (Qin & Brown, 2017). In contrast, it is incongruent with a study fulfilled in Louisiana, USA, where it was found that improving or increasing sleep hygiene knowledge is not an intervention that would be effective in improving sleep hygiene practices (Felix et al, 2017).…”
Section: Table (V)supporting
confidence: 62%
“…These sessions improved nursing students' knowledge on the importance of adopting healthy sleep hygiene practices for better sleep quality and enhanced academic performance. This finding is relatively in harmony with a study accomplished in Canada, where it was promising to find that most students reported meeting the basic needs of sleep hours and used some strategies to help their sleep (Qin & Brown, 2017). In contrast, it is incongruent with a study fulfilled in Louisiana, USA, where it was found that improving or increasing sleep hygiene knowledge is not an intervention that would be effective in improving sleep hygiene practices (Felix et al, 2017).…”
Section: Table (V)supporting
confidence: 62%
“…University students living in halls of residence face additional challenges that can further affect their quality of sleep. Problems in their sleep environment may include noise and roommates’ different habits ( Qin and Brown, 2017 ). The demands to contribute to the communal life of the hall and to integrate socially in its high-density living environment ( Zhai et al, 2018 ), the stress from short-term academic workload and long-term anxiety related to independent adult life ( Lemma et al, 2012 ; Laidlaw et al, 2016 ), and the lack of knowledge and practice of good sleep hygiene ( Suen et al, 2010 ; Dinis and Braganca, 2018 ), further add to these problems.…”
Section: Introductionmentioning
confidence: 99%
“…In one study, the prevalence of sleep disorders in Iranian University students was reported by 40.6% [ 6 ]. It appears that residency in dormitories has been cited as an influential factor that affects sleep quality in students [ 7 ]. Results of a survey from 23 countries revealed that physical activity was below the recommended levels for the majority of university students.…”
Section: Introductionmentioning
confidence: 99%